STRATEGI FORESIGHT LEADERSHIP KEPALA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER JABAR MASAGI - Dewi Tioktowati (Universitas Pendidikan Indonesia, 2021)
This study entitled Principal Foresight Strategy in Implementation of Character Education “Jabar Masagi” at state Vocational High School (SMKN) 1 Bandung. The problem that the authors have addressed in this study is about foresight strategy and implementation of character education “Jabar Masagi”. This research aims to find out how Principal implements Foresight Leadership Strategy in Character Education “Jabar Masagi” at SMKN 1 Bandung. This study use qualitative descriptive approach. Subjects of this study were a principal, teachers, and students. The data was obtained by interview and documentation study and were analyzed by reducing the data, presenting the, and concluding the data in in narrative form. The result of the study reveal that: 1) SMKN 1 Bandung has already implement Character Education “Jabar Masagi” since December 2018. The integration of each value in the Character Education “Jabar Masagi” at SMKN 1 Bandung were carried out by habituation method, the principle and teachers guidance by showing the students some set of an example, teaching and learning activity and also extracurricular activity. The implementation will not be separated by the role of the principle, teachers students and their parents. 2) In designing their future plans, principle analyze the outcome from the past experience, the outcome that met school standard and the outcome that did not met the school standard in order to get a better outcome in the future. 3) According to the characteristic of Foresight Leadership which the principle possessed, principle designing the plan to implement Character Education Program “Jabar Masagi”, any programs that related to Character Education “Jabar Masagi” were implemented by habituating the students, tutoring or counseling, and also by giving them some set of an example